A rapamycin derivative, biolimus, preferentially activates autophagy in vascular smooth muscle cells. Issue 1 (December 2018) - Kim, Yerin; Park, Jun; Seo, Jun-Hyuk; Ryu, Hyun-Seung; Lim, Kyung; Jeong, Myung; Kang, Dong; Kang, Sang
Abstract Although rapamycin is a well-known conformational inhibitor of mTORC1, it is now widely used for treating arterial restenosis. Various rapamycin analogues (rapalogue) have been made for applying to drug-eluting stents. Here we show that two major rapalogues, everolimus and biolimus, exert a differential effect on the mTORC1-mediated signaling pathways in vascular smooth muscle cells. In balloon-injured carotid arteries, both rapalogues strongly inhibit neointimal hyperplasia. Signaling pathway analyses reveal that everolimus exert cytotoxicity by increasing cellular reactive oxygen species and consequently reduce energy metabolism. By contrast, biolimus confers a preferential induction of autophagy by more strongly activating major autophagy regulator, ULK1, in vascular smooth muscle cells than everolimus does. As a consequence, the implantation of biolimus-eluting stent reduces endothelial loss, which in turn reduces inflammation, in porcine coronary arteries. Thus, this study reveals that a chemical derivatization can cause a change among mTORC1-dependent signaling pathways in vascular smooth muscle cells, thereby enabling to elicit a differential efficacy on arterial restenosis.